2020
DOI: 10.1080/17425247.2020.1814735
|View full text |Cite
|
Sign up to set email alerts
|

Vascular and extracellular matrix remodeling by physical approaches to improve drug delivery at the tumor site

Abstract: Introduction: Modern comprehensive studies of tumour microenvironment changes allowed scientists to develop new and more efficient strategies that will improve anticancer drug delivery on site. The tumour microenvironment, especially the dense extracellular matrix, has a recognised capability to hamper the penetration of conventional drugs. Development and co-applications of strategies aiming at remodelling the tumour microenvironment are highly demanded to improve drug delivery at the  Chemophototherapy, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 188 publications
(235 reference statements)
2
7
0
Order By: Relevance
“…In accordance with previous studies 40 , 41 , we found that the combined PDT could remodel the tumor microenvironment by significantly reducing the amounts of cancer associated fibroblasts (CAFs) and the density of extracellular matrix proteins, such as collagen and fibronectin (Supplementary Fig. 18 ).…”
Section: Resultssupporting
confidence: 92%
“…In accordance with previous studies 40 , 41 , we found that the combined PDT could remodel the tumor microenvironment by significantly reducing the amounts of cancer associated fibroblasts (CAFs) and the density of extracellular matrix proteins, such as collagen and fibronectin (Supplementary Fig. 18 ).…”
Section: Resultssupporting
confidence: 92%
“…Combined PDT inhibited tumor metastasis by remodeling the tumor microenvironment. In accordance with previous studies 40,41 , we found that the combined PDT could remodel the tumor microenvironment by significantly reducing the amounts of cancer associated fibroblasts (CAFs) and the density of extracellular matrix proteins, such as collagen and fibronectin (Supplementary Fig. 12).…”
Section: Quantitative Imaging Of Extracellular and Intracellular Distribution Of Nanoparticles In Different Tumorssupporting
confidence: 91%
“…The mobility of drugs in penetrating the extracellular matrix is also limited by cell-cell adhesion, high interstitial fluid pressure, lack of convection, drug metabolism, and binding (9,40). Recent data suggest that inefficient delivery of antineoplastic drugs in the tumor environment is a novel and important contributor to chemoresistance (19,20,(41)(42)(43).…”
Section: Discussionmentioning
confidence: 99%